2010
DOI: 10.1097/naq.0b013e3181d91778
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Leadership Development Academy for RNs in Long-Term Care

Abstract: While evidence strongly suggests that nursing leadership impacts nursing home care, most nursing home (NH) RN leaders have not had the benefit of a structured educational program that emphasizes the skills necessary to effectively lead in today's complex NH environment. The University of Missouri Leadership Development Academy for RNs in Long-Term Care was developed as an innovative educational program to prepare NH RNs to become effective leaders. Early data evaluating the leadership academy suggest that part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 9 publications
0
42
1
Order By: Relevance
“…This section will present a synthesis of the relevant studies. For 20 of the studies, the researchers focused on the supervisory performance of the regulated nurses, whereas two researchers (Ericson-Lidman, Larsson, & Norberg, 2013;Vogelsmeier, Farrah, Roam, & Ott, 2010) focused on the qualities, which were similar to the described supervisory behaviors of the other researchers so "supervisory performance" was the main construct used to described the results. Table S1 in the online appendix shows the description of the studies included in the review.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This section will present a synthesis of the relevant studies. For 20 of the studies, the researchers focused on the supervisory performance of the regulated nurses, whereas two researchers (Ericson-Lidman, Larsson, & Norberg, 2013;Vogelsmeier, Farrah, Roam, & Ott, 2010) focused on the qualities, which were similar to the described supervisory behaviors of the other researchers so "supervisory performance" was the main construct used to described the results. Table S1 in the online appendix shows the description of the studies included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes ranged from 12 to 300 participants in the qualitative studies, and 332 participants in the quantitative study. The mixed method studies with samples sizes ranging from 55 to 255 (Bishop et al, 2008;Rubin, Balaji, & Barcikowski, 2009;Vogelsmeier et al, 2010) utilized interviews, focus groups and surveys and one was a program evaluation (Volgesmeiser et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study involved a 5-day residency program and a 2-day "booster" weekend 5 months after the initial training. Another study that included LTC nurses involved in direct patient care concluded that evidence exists for enhanced leadership practices following a sustained and intensive training period of 8 days over 6 months (Vogelsmeier, Farrah, Roam, & Ott, 2010). Although both intervention studies showed some measurable degree of success, they involved considerable time commitment, travel, and financial cost.…”
mentioning
confidence: 99%